Valores de referência de qualidade de metais, macroelementos e radionuclídeos em solos do oeste do Paraná - Bocardi, Juliane Maria Bergamin (2019)
The metals and the macroelements of the soils are naturally derived from the decomposition of the rocks of origin, concomitant to the variations in the intensity of the pedogenic processes. In addition, all minerals and raw materials contain radionuclides of natural origin. In this context, the current legislation requires environmental indicators, Quality Reference Values - QRV, with local or regional soil characteristics that can serve as a reference for monitoring studies. The use of values obtained in different areas of the data collection site is inappropriate, since they disregard geological, pedological and climatic differences of each scenario. The objective of this research was to determine the levels of metals, macroelements and radionuclides in preserved Soils of Environmental and Remnant Forest Preservation Units in the Paraná Basin 3 (BP3), in order to obtain natural base levels for these elements and to contribute for state legislation. Inorganic constituents were determined in 73 sampled points, among them metals, macroelements and radionuclides: Ag, Al, As, Ba, Ca, Cd, Co, Cr, Cu, Fe, K, Mg, Mn, Mo, Ni, P, Pb, Sb, V, Zn, 232Th, 238U and 40K. Inductively Coupled Plasma – Optical Emission Spectrometry (ICP-OES) and Gamma Spectrometry (GRS) techniques were used in the quantification of the elements. The QRV were obtained for metals and radionuclides in the 75th percentile. With the exception of Sb and Cu, the natural contents of all the elements studied are below the Prevention Values suggested by the National Environmental Council (CONAMA, 2009). The correlation study showed several associations between the elements that can be attributed to the origin and pedogenic nature of the soil, similarity in the size and valence of the ions and the geochemical affinities. In general, the BP3 metals, macroelements and radionuclides contents were associated with the level of soil development and basaltic volcanic spills of the Serra Geral Formation.